An adaptive SVC-video streaming scheme for mobile WiMAX networks - Keta, Khotso Hamilton (Department of Electrical Engineering, 2015)
The problem that is being addressed in this study is bandwidth fluctuation that occurs during a video stream delivery over the Mobile WiMAX network, which results in video quality degradation. To address this problem, H.264AVC/SVC coded video is used.